MACHIAVÉLISME ET PRATIQUE POLITIQUE EN AFRIQUE. Réflexion sur le régime de la Deuxième République au Congo-Kinshasa (1965-1997) - Ujock, Prof. Boniface Ukumu Khotley (IJRDO - Journal of Social Science and Humanities Research, 2019)
The Machiavellism is a thought politicizes tonic has several decades or even several centuries but having characterized the political practices in several countries. And even today, this political philosophy characterizes many régimes, notably in Africa. One of the countries that has been domineered a long time on basis of thisphilosophy stays Zaire, currently the Democratic Republic of Congo. This country knew a long period of dictatorship embodied by its ex-president, Mobutu Sese Seseko. It is at a time about one period of glory but as prominent a dark page of the history of this country. In this article, our analysis consists of two shutters. In a first time, we clarify the origin of this political thought and its development in the time and in the space. In the second shutter, we try to show in what measure, the Machiavellism, a thought been born in West, inspired Mobutu Sese Seseko during the three decades of his/her/its reign.